VALIDATION OF ISAMS RETRIEVALS OF ATMOSPHERIC-TEMPERATURE AND PRESSURE - Dudhia, A; Livesey, N; Taylor, F (1994)
The ISAMS instrument on the UARS satellite uses the pressure-modulation radiometry technique to measure a variety of middle-atmosphere parameters. The temperature and pressure are retrieved using data from two CO2 modulators giving useful results in the altitude range 15-km to 80-km (100-mb to 0.01-mb) with a vertical resolution of approximately 2.5-km and precision of a few K in temperature and a few percent in pressure. Results from the most recent processing run ('V0006') stored at the UARS Central Data Handling Facility are compared with NMC fields and LIDAR profiles. These comparisons indicate some significant biases in the ISAMS data but that the accuracy of individual profiles is generally well described by the associated error bars. Future developments are also discussed. © 1994.